Nurses’ attitude towards oral care and their practicing level for hospitalized patients in Orotta National Referral Hospital, Asmara-Eritrea: a cross-sectional study - Dagnew, Zewdi Amanuel (BMC Nurs, 2020)
BACKGROUND: Effective and routine mouth care is necessary for hospitalized patients as it helps to maintain the health of oral cavity and overall health. However, oral care is often overlooked and not prioritized in daily activity plan of nurses even when oral problems are apparent. Therefore, the aim of this study was to assess nurses’ attitude towards oral care and their practicing level for hospitalized patients. METHODS: A cross-sectional study design was conducted in adult medical-surgical department of Orotta hospital from December 2017 to January 2018. Data was collected from all (N = 73) diploma and associate nurses through face to face interview using a pretested and structured questionnaire. Kruskal-Wallis, Mann-Whitney U tests and spearman rank correlation coefficient tools were performed to analyze the data using SPSS (Version 22). RESULTS: Out of the 79 participants, 73 completed the interview successfully with a response rate of 92.4%. Of the total, 56.2% were diploma nurses and 43.9% were associate nurses. The median attitude score was 68.89/100 (IQR = 48.89). The majority (94.5%) of the nurses agreed that oral cavity assessment is nurse’s responsibility and 94.5% reported adequate training is needed to provide quality oral care. On the other hand, the median practice score was 50.00/100 (IQR = 17.86). Majority of the participants (76.7%) did not perform routine oral health assessment. Almost all (98.4%) used gauze and normal saline for oral care. Practice score was significantly different across the various wards (p < 0.001), however, it was not significantly correlated with attitude (p = 0.646). CONCLUSIONS: The participants had poor level of oral care practice to hospitalized patients, nevertheless, they had favourable attitude. Therefore, Orotta National Referral Hospital needs to give further effort to train the nursing staff, ensure the availability of adequate oral care equipment and provide clear guidelines regarding oral care of hospitalized patients.